The Development of Synergy of Value in Supply Chain Collaboration Among Manufacturing Enterprises, Retail Operators and Distribution Center - ธนเสน, ณัฐวุฒิ (RMUTT Global Business and Economics Review, 2014)
The objectives of the research were: 1) to study management system, collaboration in the supply chain so that the entrepreneur would have a better understanding, 2) to study the problems of supply chain management System and find the ways to solution of the problems caused by supply chain management system among The Manufacturing Enterprises, Operators of retail and Operators of the distribution Center, and 3) to study the cause of the problems. The limitation solving, the problem and find the appropriate model for management system of the supply chain as wellThe area of study was mainly based on the overseas study in the special administrative region, in Shanghai, the People’s Republic of China. The samples were the Executives of Lotus Super center chain store, China, Manufacturing Enterprises, Operators of Distribution Center, Operators of Retails, and a group of Experts. In order to accomplish the objectives, mixed methods of research were applied through the combination of the qualitative research as the main part and the quantitative research as the supporting one. The in-depth interview of key informants selected purposively from five groups of Executives, among them were the top administrators and executives of Lotus Super Chain Stores in Shanghai, the People’s Republic of China, Manufacturing Enterprises and Distribution Center to contribute the concept of the synergic management at the real time of performance in order to develop the synergy of value of the supply chain collaboration, in Manufacturing Enterprises, Operators of Distribution Center, Operators of Retails for supporting the ideas of synergy of values. Four Hundredoperators, experts, in the three-party in supply chain. The synergy of valuescontributed their responds for the questionnaires which provided data to be collected and analyzed statistically through Pearson’s analysis.Findings were the synergy of values of three party in supply chain needed to develop their technology together. The information system should be accreted at the real time, the systems of the software technology application should be a product of join development in order to reduce and to solve the problems in computer productions, to avoid competition but to promote cooperation, instead, more over the findings would lead to development of the new model in synergy of the values for the supply chain as the so called “Jo’s Synergy Value Chain Model”